Activatable Protein Nanoparticles for Targeted Delivery of Therapeutic Peptides. Issue 7 (8th January 2018) - Yu, Xi; Gou, Xingchun; Wu, Peng; Han, Liang; Tian, Daofeng; Du, Fengyi; Chen, Zeming; Liu, Fuyao; Deng, Gang; Chen, Ann T.; Ma, Chao; Liu, Jun; et al.
Abstract: Clinical translation of therapeutic peptides, particularly those that require penetration of the cell membrane or are cytolytic, is a major challenge. A novel approach based on a complementary mechanism, which has been widely used for guided synthesis of DNA or RNA nanoparticles, for de novo design of activatable protein nanoparticles (APNPs) for targeted delivery of therapeutic peptides is described. APNPs are formed through self‐assembly of three independent polypeptides based on pairwise coiled‐coil dimerization. They are capable of long circulation in the blood and can be engineered to target diseases. Peptides to be delivered are incorporated into APNPs and released into the disease microenvironment by locally enriched proteases. It is demonstrated that APNPs mediate efficient delivery of NR2B9c, a neuroprotective peptide that functions after cell penetration, and melittin, a cytolytic peptide that perturbs the lipid bilayer, for effective treatment of stroke and cancer, respectively. Due to their robust properties, simple design, and economic costs, APNPs have great potential to serve as a versatile platform for controlled delivery of therapeutic peptides. Abstract : Clinical translation of therapeutic peptides, particularly those that require penetration of the cell membrane or are cytolytic, is a major challenge. A novel approach for de novo design of "activatable" protein nanoparticles (APNPs) for targeted delivery of peptides is described. It is demonstrated that APNPs safely deliver therapeutic peptides regardless of their toxicity for effective disease treatment.